2011
DOI: 10.1177/0363546511415660
|View full text |Cite
|
Sign up to set email alerts
|

Functional and Structural Outcomes of Single-Row Versus Double-Row Versus Combined Double-Row and Suture-Bridge Repair for Rotator Cuff Tears

Abstract: The additional suture bridges decreased the retear rate for large and massive tears. The combination of the double-row and suture-bridge techniques, which had the lowest rate of postoperative retear, is an effective option for arthroscopic repair of the rotator cuff tendons because the postoperative functional outcome in patients with a retear is inferior to that without retear.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
126
1
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 178 publications
(136 citation statements)
references
References 46 publications
7
126
1
2
Order By: Relevance
“…A modification of the double-row technique is the double-row suture bridge technique [36,[53][54][55][56] . Gartsman et al [54] , evaluated the repair integrity of single-row vs double-row suture bridge arthroscopic rotator cuff repairs in a prospective, randomized study.…”
Section: Muscle-tendon Unit Retractionmentioning
confidence: 99%
See 2 more Smart Citations
“…A modification of the double-row technique is the double-row suture bridge technique [36,[53][54][55][56] . Gartsman et al [54] , evaluated the repair integrity of single-row vs double-row suture bridge arthroscopic rotator cuff repairs in a prospective, randomized study.…”
Section: Muscle-tendon Unit Retractionmentioning
confidence: 99%
“…They demonstrated that double-row suture bridge repair resulted in a significantly higher tendon healing rate compared to arthroscopic single-row repair. Mihata et al [53] demonstrated that in the subcategory of large and massive rotator cuff tears, the re-tear rate in the double-row suture bridge group was significantly less than those in the single-row group and the nonsuture bridge double-row group. Several techniques have been described for double row suture bridge repair.…”
Section: Muscle-tendon Unit Retractionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although considerable symptomatic improvement is possible in the absence of complete anatomic healing, 2,6,8,24 these 2 new studies and others 14,16,22,24,30 suggest a link between the 2 metrics of success, a link that may be more manifest as time goes on. While they both support the conclusion that relatively short follow-up is sufficient when the measured end point is primary structural integrity, they also attest to the benefit of a longer perspective for evaluation of symptomatic improvement.…”
mentioning
confidence: 91%
“…Nevertheless, none of these advances has brought significant improvement to the quality of healing and postoperative results, especially in patients with large rotator cuff injuries [9,10]. In large lesions there are often unsatisfactory long term results and many studies show a high percentage of re-ruptures (11-94 %) [11][12][13]. High rates of the tendon injury and re-rupture accelerate investigations of methods modulating tendons healing.…”
Section: Introductionmentioning
confidence: 99%